Justice and Legal Certainty in Regulating Cryptocurrency in Malaysia - Muhamad Marwan; Galang Prayogo (APPTHI, 2019)
Cryptocurrencies have received important attention as alternative mediums of exchange that can complement or even replace traditional ones. For this reason, cryptocurrencies have become an attractive investment vehicle with a constantly growing market cap. Cryptocurrencies’ role and economic impact cannot be concluded further than just a disruptive technology to the conventional financial system. The unstable and highly speculative value fluctuations coupled with a relatively new technological system have resulted in a lack of research to predict the future cryptocurrency market development. The research method used in this legal research is the juridical-normative method. The juridical-normative method is intended to seek or find rules, principles, and legal doctrines, which are then applied to analyze a phenomenon that is a legal subject. The presence of cryptocurrency has its own impact on social life. These impacts stem from the main feature of cryptocurrencies, the blockchain. Blockchain offers a revolution in the paradigm of the financial system, which was initially centered on the existence of central authorities such as governments and banks to become user-centered or user-centered. In addition, the philosophical values applied in cryptocurrency and blockchain reflect ideas that are synonymous with the collegial collective spirit, such as decentralization, transparency, equality, and accountability. Abstrak Mata uang kripto telah mendapat perhatian penting sebagai media pertukaran alternatif yang dapat melengkapi atau bahkan menggantikan yang tradisional. Karena alasan ini, Mata uang kripto telah menjadi sarana investasi yang menarik dengan kapitalisasi pasar yang terus berkembang. Untuk saat ini, peran dan dampak ekonomi dari Mata uang kripto tidak dapat disimpulkan lebih jauh dari sekadar teknologi yang mengganggu sistem keuangan konvensional. Fluktuasi nilai yang tidak stabil dan sangat spekulatif ditambah dengan sistem teknologi yang relatif baru mengakibatkan kurangnya penelitian untuk memprediksi perkembangan pasar Mata uang kripto di masa depan. Metode penelitian yang digunakan dalam penelitian hukum ini adalah metode yuridis normatif. Metode yuridis-normatif dimaksudkan untuk mencari atau menemukan kaidah, asas dan doktrin hukum yang kemudian diterapkan untuk menganalisis suatu fenomena yang menjadi subjek hukum. Kehadiran cryptocurrency memiliki dampak tersendiri dalam kehidupan sosial. Dampak ini berasal dari fitur utama Mata uang kripto, blockchain. Blockchain menawarkan revolusi paradigma sistem keuangan yang awalnya berpusat pada keberadaan otoritas pusat seperti pemerintah dan bank menjadi user-centered atau berpusat pada pengguna. Selain itu, nilai-nilai filosofis yang diterapkan dalam cryptocurrency dan blockchain mencerminkan ide-ide yang identik dengan semangat kolektif kolegial seperti desentralisasi, transparansi, kesetaraan, dan akuntabilitas. Kata kunci: Mata uang kripto, Bitcoin, Hukum, Ekonomi, Malaysia